New nomenclatural combinations for taxa of Pentanema (Asteraceae) occurring in Ukraine - Boiko, G.V.; Korniyenko, O.M.; Mosyakin, S.L. (Український ботанічний журнал, 2018)
Recent molecular phylogenetic results demonstrated that the genus Inula in its traditional circumscription is polyphyletic and its type, I. helenium, belongs to a clade phylogenetically distant from the clade containing the majority of species earlier placed in Inula. The nomenclatural proposal to conserve the generic name Inula with I. hirta as the conserved type has not been adopted. Because of that the genus Inula s. str. now comprises ca. 5 species (I. helenium and its relatives). The genus Pentanema was considerably re-circumscribed to include most of taxa earlier treated in Inula. Several taxa of Inula s.l. occurring in Ukraine, however, did not have respective names available in Pentanema, but such names are needed for the forthcoming checklist of vascular plants of Ukraine (in preparation). The following new nomenclatural combinations are validated: Pentanema asperum (Poir.) G.V.Boiko & Korniyenko, comb. nov. (Inula aspera Poir.), P. caspicum (F.K.Blum) G.V.Boiko, Korniyenko & Mosyakin, comb. nov. (I. caspica F.K.Blum in Ledeb.), P. × medium (M.Bieb.) G.V.Boiko & Korniyenko, comb. nov. (I. media M.Bieb.), and P. sabuletorum (Czern. ex Lavrenko) G.V.Boiko & Korniyenko, comb. nov. (I. sabuletorum Czern. ex Lavrenko). Additionally, two new subspecies-rank combinations, P. salicinum (L.) D. Gut.Larr. et al. subsp. asperum (Poir.) Mosyakin and P. salicinum subsp. sabuletorum (Czern. ex Lavrenko) Mosyakin, comb. nov., are proposed by the third author.